Structurally distinct telomere-binding proteins in Ustilago maydis execute non-overlapping functions in telomere replication, recombination, and protection - Eun Young Yu (Nature Portfolio, 2020)
Yu et al. provide evidence that Ustilago maydis employs two structurally distinct telomere-binding proteins to perform complementary functions in telomere maintenance in this organism. While UmTay1 regulates primarily telomere replication and recombination, UmTrf2 is responsible for telomere protection.